Level of knowledge about patient rights and level of empathy among general practitioners in Lambayeque, Peru - Malca-Diaz, Jimmy Fernando (2025)
Respecting patient rights and establishing a relationship based on empathy is very important in a physician's professional practice, but some studies report low levels. This can lead to an increase in legal and ethical issues and dissatisfaction with patient care. Furthermore, there is an urgent need to humanize healthcare, and to achieve this, physicians must be empathetic and aware of patient rights. This study seeks to describe the level of knowledge about patient rights and the level of empathy among general practitioners in Lambayeque, Peru. To this end, a descriptive, cross-sectional, and observational study was conducted. The study involved a population of 310 general practitioners registered in Lambayeque, Peru; the sample consisted of 255 physicians. A questionnaire was administered to assess knowledge of patient rights, in addition to the Jefferson Physician Empathy Scale. The data collected in April and May 2024 were processed using SPSS version 25 software, revealing that 94.9% of general practitioners had a high level of knowledge about patient rights and 78.4% had a medium level of empathy. These findings suggest that general practitioners displayed adequate knowledge about patient rights; however, their level of empathy was medium, which needs to be improved due to its impact on patient care. Furthermore, these aspects should be learned and practiced throughout medical training through ethics and bioethics courses.